First equilibrium reconstruction for ITER with the code NICE. (1st February 2022) - Faugeras, B.; Blum, J.; Boulbe, C.
Abstract: In this short paper we present the first application of the IMAS compatible code NICE to equilibrium reconstruction for ITER geometry. The inverse problem is formulated as a least square problem and the numerical methods implemented in NICE in order to solve it are presented. The results of a numerical experiment are shown: a reference equilibrium is computed from which a set of synthetic magnetic measurements are extracted. Then these measurements are used successfully to reconstruct the equilibrium of the plasma.